Fourth contribution to the Macratriinae LeConte, 1862 of the Papuan Region and Wallacea (Coleoptera: Anthicidae) with descriptions of sixteen new species - Telnov, Dmitry (Zootaxa, 2023)
Descriptions of the following 16 new species of Macratriinae LeConte, 1862 are presented based on the material from various scientific institutions: Macratria anus, M. bimaculosa, M. bonggo, M. koiari, M. korowai, M. kundratai, M. longitarsis, M. perkovskyi, M. ripicola, M. roosilehti, M. saccharum, M. sentani, M. spatulatocalcarata, M. susuami, M. tigrina, M. tongkonan spp. nov. New distribution records of eight Macratria Newman, 1838 species are provided.